Absolute and age-dependent elevations of serum calcium and phosphate and their products in clinical opiate dependence. (March 2014) - Reece, Albert Stuart
<x xml:space="preserve">Abstract</x> Context: Chronic opiate dependence has been linked with premature appearance of many chronic age-related disorders and blood-borne biomarkers of ageing. Objective: To determine if clinical opiate substance use disorder (SUD) was associated with elevations of serum calcium and phosphate and their various products. Methods: Chemical pathology records were traced retrospectively. Results: A total of 1747 SUD patients were compared with 6454 non-SUD (NSUD) patients. The mean (±SD) ages were 32.06 ± 6.64 and 32.13 ± 8.12 years, respectively (p = 0.74). The two groups were 69.5% and 54.6% male (p < 0.000 1). The mean serum calcium levels were 2.40 ± 0.11 and 2.37 ± 0.10 mmol/l (p < 0.000 1). This significant difference was unrelated to albumin levels, and also occurred for phosphate: 1.17 ± 0.22 and 1.15 ± 0.22 (p < 0.000 1). Both the calcium-phosphate product and the calcium-phosphate solubility product were also elevated. These elevations persisted at multiple regression against age in both additive and interactive models with age (most p < 0.000 1). At age 35, the corrected calcium and phosphate were equivalent to a 75.1% and 13.5% age advancement, respectively. Conclusion: Opiate dependence is associated with significant elevations of calcium and phosphate both in absolute terms, and after correction for serum albumin and age. Their product and their solubility product are similarly elevated.